Forensic Accounting Methods and Reducing Creative Accounting Practices: Evidence from Jordan - S. Al-Qadi, Naim; H. Al-Dmour, Ahmed (Jordan Journal of Business Administration, 2022)
This study aims to investigate the role of forensic accounting methods in reducing creative accounting practices in Jordan as a developing country. The targeted population consisted of 357 respondents from auditing accounting working in auditing offices in Amman. A self-administrated questionnaire was used as an instrument for data collection and multiple-regression analysis was employed for data analysis. The study findings indicated that three factors could be extracted from forensic accounting methods; namely, investigation operations, procedures and evaluation processes. These factors (methods) showed to have a positive relationship with reducing creativity accounting practices from auditors’ perspective in Jordan. The most crucial forensic accounting method (factor) that proved to be highly associated with reducing creativity accounting practices was the “procedures” method